Assessment of Factors Influencing Facility Management Procurement Route in Lagos State, Nigeria - Olajide, Faremi Julius.; Afolarin, Adenuga Olumide.; Beauty, John Iniobong (Journal of Surveying, Construction and Property, 2013)
Procurement of Facility Management (FM) services can be made through three main approaches; In-sourcing, Outsourcing or a combination of both In-sourcing and Outsourcing (Hybrid). The approach taken depends on the priority set by the organisation for the services to be procured amidst prevailing constraints and limitations. Many organisations follow a rule of chance approach in choosing a particular FM procurement option that seems right at the time and then wait to learn from the outcome later, this no doubt can come at a very high consequence to the organisation. This study therefore assesses the factors influencing the choice of procurement routes in facilities management. 75 structured research questionnaires were distributed, 55 were completed and returned representing a 73% response rate. The findings of this study shows that continuity and risk management are the most important factors influencing decision when considering in-house procurement route for FM services while reduced overhead and improved process responsiveness were ranked as top factors considered when outsourcing and choosing the hybrid routes respectively. It was recommended that organisations must strive to achieve efficiency in their service delivery for enhanced customer satisfaction.